Playing games to re-story troubled family narratives in Danish maximum-security prisons. (October 2020) - Markussen, Thomas; Knutz, Eva
Narrative criminology has successfully demonstrated how the construction and structure of self-narratives are important for prisoners' process of change and desistance from crime. However, much of this work has tended to focus narrowly on the offender and how he or she uses self-narrative to relate to the offense, the victim, past childhood, the family, or projected hopes for future change. In an effort to extend prior work, this study takes a complementary approach by analyzing how children and their long-term incarcerated fathers in Danish maximum-security prisons talk about family relations and cohesiveness during imprisonment. To address the gap in research and methodology, we introduce the notion of family narratives, and through microanalyses of in-depth interviews with seven prisoners and seven children, we extract three kinds of family narratives. These narratives were prompted by using a board game recently implemented into the visiting program in Danish prisons to help children and prisoners to re-construct disrupted family relations. Our findings illuminate how the design of a game can be a novel method for collecting data on children and incarcerated fathers and how family narratives can serve as lenses for studying fragile family identity, masculinity, and child–parent relations.